The future of housing finance restructuring the U.S. residential mortgage market - Baily, Martin Neil. (Washington, D.C. Brookings Institution Press, 2011)
"Evaluates the options open to policymakers as they reassess the federal government's role in the U.S. residential mortgage market and consider a new system that reduces risk in mortgage lending, maintains a limited government role, and gradually removes the government-sponsored enterprises (Fannie Mae and Freddie Mac) from the mortgage market"--Provided by publisher.
Preface -- 1. The federal role in housing finance : principal issues and policy proposals / Douglas J. Elliott -- 2. The cycle in home building / Alan Greenspan -- 3. Toward a three-tier market for U.S. home mortgages / Robert C. Pozen -- 4. Government's role in the housing finance system : where do we go from here? / Karen Dynan and Ted Gayer -- 5. Eliminating the GSEs as part of comprehensive housing finance reform / Peter J. Wallison -- 6. Catastrophic mortgage insurance and the reform of Fannie Mae and Freddie Mac / Diana Hancock and Wayne Passmore -- 7. The economics of housing finance reform / David Scharfstein and Adi Sunderam.
Keywords: Federal National Mortgage Association; Freddie Mac (Firm); Mortgage loans -- Government policy -- United States; Housing -- United States -- Finance